Cafeicultura e transformações socioespaciais no município de Alfenas-MG pós-inundação pelo lago de furnas - Costa, Tamyris Maria Moreira Da (2023)
Since the beginning of its formation, at the end of the 18th century, the municipality of Alfenas/MG went through transformations that affected its demographic and socioeconomic dynamism, especially as of the 1960's, with the flooding of part of its lands by the waters of the reservoir resulting from the implementation of the Furnas hydroelectric power plant, affecting more than 34 municipalities in southern Minas Gerais. From that moment on, changes occurred in the main economic activity, with the loss of fertile floodplains, so the existing productive logic gave way to coffee farming. Thus, this research sought to understand the socio-spatial transformations in the municipality of Alfenas-MG, with emphasis on the expansion of coffee farming, after the flooding of rural areas affected by the Furnas Lake. In order to carry it out, we chose as methodological procedure the bibliographic review on the theme, the survey of secondary data (IBGE) and documentary data (CEDOC-UNIFAL-MG), the elaboration of maps of land use, from the MapBiomas platform and, finally, the field work to get to know the rural properties affected by the lake waters and, through the interviews with the coffee growers who experienced the transformations, we can see advances in coffee farming, such as the insertion of machinery, reduction of labor and expansion of farming areas. The consolidation was a difficult process, considering the changes from supply agriculture to the production of a commodity, it took years overcoming the uncertainties and the new challenges imposed by this new local-regional reality, which currently places Alfenas among the Arabica coffee producing cities in the country. However, for the farmers who experienced these transformations, the hope for better days was and still is what keeps them in this activity.